Challenges and breakthroughs: current landscape and future prospects of CAR-T cell therapy clinical trials for solid tumors - Guo, Jing; Zhou, Chunhe; Zhao, Hongmei; Li, Huiyan (Frontiers in Oncology, 2025)
Chimeric antigen receptor T-cell (CAR-T) therapy has demonstrated significant efficacy in the treatment of hematological malignancies; however, its application in the solid tumor setting remains challenging. Given that solid tumors account for the vast majority of clinically diagnosed cancers, there is an urgent and significant clinical need to develop effective CAR-T therapy. This review focuses on the latest clinical trials of CAR-T therapy in major solid tumors, including glioma, colorectal, pancreatic, prostate, and lung cancers. It systematically evaluates the results of studies targeting key tumor-associated antigens, such as EGFR, IL13Rα2, GD2, B7-H3, CEA, MSLN, PSCA/PSMA, and ROR1. The results indicate that locally delivered, dual-targeted CAR-T cells and engineered CAR-T cells show potential in reducing antigenic escape and enhancing cellular function. Significant survival benefit and tumor remission were observed in some studies. However, antigen heterogeneity-driven escape, tumor immunosuppressive microenvironment, insufficient persistence of CAR-T cells in vivo, and treatment-related toxicity still limit their efficacy and clinical application. To address these challenges, we further discuss various optimization strategies, including target selection, combination of immune checkpoint inhibitors or tumor microenvironment modulators, and optimization of CAR structural design and delivery methods. In the future, through the exploration of multi-dimensional optimization design and combination therapeutic regimen, it is expected to facilitate the broader application and clinical translation of CAR-T therapy in solid tumor treatment.